STRATEGY SELECTION ON SOFTWARE INDUSTRY BASED ON GE MULTI-FACTORS PORTFOLIO MATRIX - Rufman Imam Akbar; Muh. Mardiyana; Slamet Riyanto (SISFOTENIKA, 2013)
Abstract:Strategy Selection on Software Industry Based on Ge Multi-Factors Portfolio Matrix. Based on some data, we found that half of software project had been fail to fulfill their needs for information processing, storage, search, and retrieval. Almost 53 percent were completed, but they were over-budget and over-schedule and did not meet the original specifications. Even most of the problem came from process of the development – the impact are to software industry. This study try to apply GE Multifactors Portfolio Matrix on Software Industry to see position based on Business Strength and Industry Attractiveness.